2017
DOI: 10.1111/joim.12657
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient palliative care referral and 9‐month hospital readmission in patients with congestive heart failure: a linked nationwide analysis

Abstract: Patients with HF who received an inpatient PC visit had significantly lower rates of all-cause and HF-specific readmission in the subsequent 9 months. Total 9-month hospital charges were also significantly lower for patients who received an inpatient PC visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…Forty of the 43 identified studies were non-intervention studies, using the following methods: national registry/chart review (Arestedt et al, 2018;Bakitas et al, 2017;Connor, Pyenson, Fitch, Spence, & Iwasaki, 2007;Formiga, Espel, Chivite, & Pujol, 2002;Johnson, Parsons, Raw, Williams, & Daley, 2009;Thorns, Gibbs, & Gibbs, 2001;Unroe et al, 2011;Zambroski et al, 2005), interviews (Gerlich et al, 2012;Glogowska et al, 2016;Gott et al, 2008;Hupcey, Penrod, & Fenstermacher, 2009;Kavalieratos, Mitchell et al, 2014;Kimani, Murray, & Grant, 2018;Murray et al, 2007;Selman, Beattie, Murtagh, & Higginson, 2009), retrospective surveys/questionnaire studies (Davidson, Abernethy, Newton, Clark, & Currow, 2013;Kuragaichi et al, 2018;Malik, Gysels, & Higginson, 2013;Mizuno et al, 2016;Wiskar, Celi, Walley, Fruhstorfer, & Rush, 2017), data analysis studies (Chattoo & Atkin, 2009;Greener, Quill, Amir, Szydlowski, & Gramling, 2014;Janssens & Reith, 2013;Mandawat, Heidenreich, Mandawat, & Bhatt, 2016), descriptive study (Abarshi et al, 2010;Cheung et al, 2013;Davidson et al, 2004;Formiga et al, 2008;Greener et al, 2014;Lagman, Walsh, Kunkle, LeGrand, & Davis, 2006;MartÃ-n-Lesende et al, 2016), a retrospective case-control study (Haydar, Lowe, Kahveci, Weatherford, & Finucane, 2004), observational studies …”
Section: Resultsmentioning
confidence: 99%
“…Forty of the 43 identified studies were non-intervention studies, using the following methods: national registry/chart review (Arestedt et al, 2018;Bakitas et al, 2017;Connor, Pyenson, Fitch, Spence, & Iwasaki, 2007;Formiga, Espel, Chivite, & Pujol, 2002;Johnson, Parsons, Raw, Williams, & Daley, 2009;Thorns, Gibbs, & Gibbs, 2001;Unroe et al, 2011;Zambroski et al, 2005), interviews (Gerlich et al, 2012;Glogowska et al, 2016;Gott et al, 2008;Hupcey, Penrod, & Fenstermacher, 2009;Kavalieratos, Mitchell et al, 2014;Kimani, Murray, & Grant, 2018;Murray et al, 2007;Selman, Beattie, Murtagh, & Higginson, 2009), retrospective surveys/questionnaire studies (Davidson, Abernethy, Newton, Clark, & Currow, 2013;Kuragaichi et al, 2018;Malik, Gysels, & Higginson, 2013;Mizuno et al, 2016;Wiskar, Celi, Walley, Fruhstorfer, & Rush, 2017), data analysis studies (Chattoo & Atkin, 2009;Greener, Quill, Amir, Szydlowski, & Gramling, 2014;Janssens & Reith, 2013;Mandawat, Heidenreich, Mandawat, & Bhatt, 2016), descriptive study (Abarshi et al, 2010;Cheung et al, 2013;Davidson et al, 2004;Formiga et al, 2008;Greener et al, 2014;Lagman, Walsh, Kunkle, LeGrand, & Davis, 2006;MartÃ-n-Lesende et al, 2016), a retrospective case-control study (Haydar, Lowe, Kahveci, Weatherford, & Finucane, 2004), observational studies …”
Section: Resultsmentioning
confidence: 99%
“…The use of robotic surgery was captured with ICD9 procedure code 17.4. Using a previously described approach to the NRD, we included patients who underwent surgery in the first 10 months of each year (2012‐2014) of the NRD to allow for adequate follow‐up time . Each patient was followed for a fixed period of 60 days from the date of discharge from ther index hospitalization for readmission to allow for analysis of 30‐readmission as well as 60‐day readmission.…”
Section: Methodsmentioning
confidence: 99%
“…Using a previously described approach to the NRD, we included patients who underwent surgery in the first 10 months of each year (2012-2014) of the NRD to allow for adequate follow-up time. [24][25][26] Each patient was followed for a fixed period of 60 days from the date of discharge from ther index hospitalization for readmission to allow for analysis of 30-readmission as well as 60-day readmission. We did not count readmissions for neck dissections alone without codes for other complications because these patients were likely planned readmissions for staged procedures.…”
Section: Cohort Selectionmentioning
confidence: 99%
“…Readmissions were further decreased when consults included goals of care discussions; however, readmissions were not affected when consults involved symptom management alone. Wiskar et al (2017) conducted a study using a retrospective secondary data analysis design to analyze data in the Nationwide Readmission Database (NRD). The NRD gathers all hospital admissions from 22 states, tracks those patients through the hospital, and allows for the examination of data for readmission rates.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…(2016) had a majority of Black patients within the study. Two studies focused on patients with HF (Chuang, Kim, Blank, Southern & Fausto, 2017;Wiskar, Celi, Walley, Fruhstorfer, & Rush, 2017), two studies had the majority of patients with septicemia (Bharadwaj, et al, 2016;Zalenski, et al, 2016), two studies focused on oncology patients Zhang, et al, 2017), the other studies did not have a specific patient population identified, but used a trigger for a PC consult (Gagne Henderson et al, 2017;Lathrop, & Gottfried, 2015).…”
Section: Study Characteristics and Participantsmentioning
confidence: 99%